The Role of Judy Hopps in Nick Wilde's Character Development in Zootopia (2016) - Fani Aulitha Putri (Institute of Advanced Knowledge and Science, 2026)
This study investigates the role of Judy Hopps in Nick Wilde’s character development in Zootopia (2016). While previous studies have primarily focused on stereotypes and discrimination portrayed in the film, limited attention has been given to the interpersonal factors that drive Nick’s transformation. Therefore, this research aims to analyze how Judy Hopps contributes to Nick Wilde’s development from an egoistic and cynical individual into a sympathetic and socially responsible character. This study employs a descriptive qualitative method using M. H. Abrams’ characterization theory and E. M. Forster’s concept of round characters. The data were collected from dialogues, actions, and interactions between Judy Hopps and Nick Wilde throughout the film and analyzed using Miles and Huberman’s interactive model. The findings reveal that Judy plays a crucial role in Nick’s transformation by acting as a trust provider, stereotype challenger, moral model, vulnerable partner, and reinforcer of positive identity. Through consistent trust, acceptance, and empathy, Judy gradually helps Nick overcome his negative self-perceptions and defensive attitudes formed by past discrimination. As a result, Nick develops greater empathy, responsibility, and commitment to social values. The study concludes that Judy Hopps serves as the primary catalyst for Nick Wilde’s character development, demonstrating how positive interpersonal relationships can encourage personal growth and challenge internalized prejudice.